A Case of Unnecessary Panic: Dengue Infection during Anti-TNF Treatment for Psoriasis. Issue 4 (September 2017) - Luna, Paula Carolina; Arias, Cintia Maricel; Manggiarotti, German Gastón; Castro Pérez, Gimena Antonia; Mazzuoccolo, Luis Daniel
We report a patient who was infected by dengue virus during a rare epidemic in Argentina. As he was receiving anti-TNF therapy for psoriasis, we were afraid he might have a bad outcome. The patient had a good resolution, however, and a literature review showed that while TNF plays a very important role in the development of dengue fever symptoms, the use of anti-TNF drugs seems not to worsen the course of the disease, and might even protect patients from severe disease.